2018
DOI: 10.1159/000489021
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of Programmed Death-Ligand 1 in Infiltrating Immune Cells in Hepatocellular Carcinoma Tissues after Sorafenib Treatment

Abstract: Objective: Programmed death-ligand 1 (PD-L1) expression in the tumor microenvironment (TME) has been reported to be related to prognosis in patients with hepatocellular carcinoma (HCC) after hepatectomy. The impact of sorafenib on PD-L1 expression in the TME of advanced HCC is unclear. Patients and Methods: Patients with HCC who received sorafenib for advanced disease at National Taiwan University Hospital, Taipei, Taiwan, and who had paired HCC tissues obtained before and after sorafenib treatment were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 31 publications
3
35
0
Order By: Relevance
“…It was found that PD‐L1 expression on 4T1 cells was higher in post‐treatments than in pretreatments. Previous work also indicated that PD‐L1 expression on the tumor cell surface was higher in post‐treatment than that in pretreatment . All samples regardless of treatment expressed PD‐L1 (Figure b).…”
Section: Methodssupporting
confidence: 50%
“…It was found that PD‐L1 expression on 4T1 cells was higher in post‐treatments than in pretreatments. Previous work also indicated that PD‐L1 expression on the tumor cell surface was higher in post‐treatment than that in pretreatment . All samples regardless of treatment expressed PD‐L1 (Figure b).…”
Section: Methodssupporting
confidence: 50%
“…The expression of PD-L1 itself is strongly placed under the transcriptional regulation of hypoxia inducible factor 1-alpha [129]. In HCC, sorafenib therapy induces tumoural PD-L1 overexpression [130], and pre-clinical evidence in mouse models suggests this to correlate with T-reg accumulation and M2-macrophage polarisation through hypoxia, drawing a translationally appealing rationale for combination therapy [131]. Inhibition of tumour angiogenesis, and in particular VEGF aids normalisation of the endothelial barrier by regulating key adhesion molecules for immune cell homing to the tumour.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…32 This suggests that sorafenib treatment may recruit T cells to the tumor and then elicit PD-L1 expression (possibly by expression of interferon-γ). For example, it has been reported that PD-L1 expression in HCC samples increases after treatment with sorafenib.…”
Section: Hcc and Immunomodulationmentioning
confidence: 99%
“…For example, it has been reported that PD-L1 expression in HCC samples increases after treatment with sorafenib. 32 This suggests that sorafenib treatment may recruit T cells to the tumor and then elicit PD-L1 expression (possibly by expression of interferon-γ). To the best of our knowledge, the mechanism of this change remains to be elucidated and may be related to the type of cell death induced by sorafenib or the inhibition of specific tyrosine kinases such as vascular endothelial growth factor receptor.…”
Section: Hcc and Immunomodulationmentioning
confidence: 99%